Sensor-based behavioral patterns can identify heat-sensitive lactating dairy cows - G. Ranzato; I. Lora; B. Aernouts; I. Adriaens; F. Gottardo; G. Cozzi (International Journal of Biometeorology, 2023)
Heat stress impairs the health and performance of dairy cows, yet only a few studies have investigated the diversity of cattle behavioral responses to heat waves. This research was conducted on an Italian Holstein dairy farm equipped with precision livestock farming sensors to assess potential different behavioral patterns of the animals. Three heat waves, defined as at least five consecutive days with mean daily temperature-humidity index higher than 72, were recorded in the farm area during the summer of 2021. Individual daily milk yield data of 102 cows were used to identify “heat-sensitive” animals, meaning the cows that, under a given heat wave, experienced a milk yield drop that was not linked with other health events (e.g., mastitis). Milk yield drops were detected as perturbations of the lactation curve estimated by iteratively using Wood’s equation. Individual daily minutes of lying, chewing, and activity were retrieved from ear-tag-based accelerometer sensors. Semi-parametric generalized estimating equations models were used to assess behavioral deviations of heat-sensitive cows from the herd means under heat stress conditions. Heat waves were associated with an overall increase in the herd’s chewing and activity times, along with an overall decrease of lying time. Heat-sensitive cows spent approximately 15 min/days more chewing and performing activities ( p < 0.05). The findings of this research suggest that the information provided by high-frequency sensor data could assist farmers in identifying cows for which personalized interventions to alleviate heat stress are needed.

Density and habitat use of lions and spotted hyenas in northern Botswana and the influence of survey and ecological variables on call-in survey estimation - G. Cozzi; F. Broekhuis; J. W. McNutt; B. Schmid (Biodiversity and Conservation, 2013)

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

Fumonisin B 2 production by Aspergillus niger from grapes and natural occurrence in must - A. Logrieco; R. Ferracane; M. Haidukowsky; G. Cozzi; A. Visconti; A. Ritieni (Food Additives & Contaminants: Part A, 2009)

Distinct Na+/K+/2Cl- cotransporter localization in kidneys and gills of two euryhaline species, rainbow trout and killifish - Fumi Katoh; Regina R. F. Cozzi; William S. Marshall; Greg G. Goss (Cell and Tissue Research, 2008)

Is PM10 mass measurement a reliable index for air quality assessment? An environmental study in a geographical area of north-eastern Italy - F. Cozzi; G. Adami; P. Barbieri; E. Reisenhofer; M. Bovenzi (Environmental Monitoring and Assessment, 2008)

Mid and Near Infrared Spectroscopy to Identify Illegal Treatments in Beef Cattle - P. Berzaghi; S. Segato; G. Cozzi; I. Andrighetto (Veterinary Research Communications, 2006)

Detection and Identification of cry1I Genes in Bacillus thuringiensis Using Polymerase Chain Reaction and Restriction Fragment Length Polymorphism Analysis - Diego H. Sauka; Jorge G. Cozzi; Graciela B. Benintende (Current Microbiology, 2006)

Effect of Plant Maturity and Germplasm on in situ Rumen Degradability and Rate of Passage of Alfalfa Hay - M. Dorigo; F. Gottardo; P. Berzaghi; G. Cozzi (Veterinary Research Communications, 2005)

Screening of cry2 genes in Bacillus thuringiensis isolates from Argentina - Diego H. Sauka; Jorge G. Cozzi; Graciela B. Benintende (Antonie van Leeuwenhoek, 2005)

Characterization of INTA 51-3, a New Atypical Strain of Bacillus thuringiensis from Argentina - Graciela B. Benintende; Joel E. López-Meza; Jorge G. Cozzi; Carlos F. Piccinetti; Jorge E. Ibarra (Current Microbiology, 2000)

Aquifer-induced Seismicity in the Central Apennines (Italy) - F. Bella; P. F. Biagi; M. Caputo; E. Cozzi; G. Della Monica; A. Ermini; W. Plastino; V. Sgrigna (Pure and Applied Geophysics, 1998)